Знахідки римських монет на Волині: основні категорії та особливості розповсюдження (до проблеми регіонального вивчення) - Мизгін, К.В. (Археологія і давня історія України, 2019)
На підставі опублікованих та нових джерел
розглядаються різні категорії нумізматичних
знахідок римського часу на території Волині, виокремлюються особливості їх розповсюдження у
порівнянні з іншими регіонами Центральної та Східної Європи. The article is an experience of regional study of Roman
coins finds on the territory of Eastern Europe. The
basic information about them was collected and published
in the middle of the 20th century. However, today
this source base has significantly expanded. Basically,
due to the use of metal detectors during archaeological
research and, unfortunately, for illegal purposes
(such finds are called «less reliable», their use is obligatory,
however, provided a critical approach to information).
Analysis of the main categories of Roman
coins finds in the region made it possible to distinguish
features in their distribution. Basically, Volhynia are is outside the concentration of the main categories of
finds of Roman coins in Eastern Barbaricum: Roman republican coins, 1—2nd c. AD denarii, 1—3rd c. AD aurei,
2—3rd AD bronze provincial coins, antoniniani and bronze and silver emissions of 4th c. AD. Nevertheless,
the concentration of the 4th c. AD Roman gold medallions is associated with this region (in article published
a new find of such coin), which indicates here the existence of the centre of the barbarous elite. In general, the
numismatic material of the Volhynia region is typical for the territory of the right bank of Dnieper. At the
same time, do not forget that Volhynia, like all territory of Eastern Barbaricum, in Roman period was part
of the German cultural circle, in which Roman coins were universal.